Development of Natural Science Practicum Instructions Based Coastal Community Environment - Mardalina, Fitriya; Herowati, Herowati; Hidayat, Jefri Nur (N A T U R A L: Jurnal Ilmiah Pendidikan IPA, 2022)
The problems experienced by students of class IX SMPN 5 Sumenep are (1) the IPA practical instructions do not contain the components clearly and completely, (2) the practical instructions used in class IX have not been integrated with the environment of coastal communities. This makes the learning process less meaningful for students. The purpose of this study was to determine the feasibility and response of students to the practical guidelines for science-based coastal community environment. This research is a research and development (Research and Development) using the 4-D model. The data collection instrument used consisted of product eligibility instruments and student response instruments. Initial testing (Initial Testing) was carried out on 5 students and quantitative testing (Quantitative Testing) was carried out on 31 Students. The feasibility results of the IPA-based environmental practicum guide from the validation of material aspects, and the design obtained an average of 100% with a very decent category. The results of students' responses to the IPA-based practicum guidelines for coastal communities obtained a percentage of 95% with a very good category so that the IPA-based practicum guides for coastal communities are very appropriate to be used as teaching materials for carrying out practical activities.